Development Strategy for Local Community Empowerment Through the Implementation of the Mami Sera (Mangunharjo Mandiri Sejahtera) Program: CSR of Pertamina Patra Niaga AFT Ahmad Yani - Zuliana Risky Amalia; Bulan Prabawani; Febri Saktiani (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study explores development strategies to empower local communities through the implementation of the MAMI SERA (Mangunharjo Mandiri Sejahtera) program, a Corporate Social Responsibility (CSR) initiative by PT Pertamina Patra Niaga AFT Ahmad Yani. This program aims to improve the economic, social, and environmental welfare of the Mangunharjo community in Semarang, which faces significant environmental challenges such as coastal erosion and flooding. This study uses qualitative methods with interview, observation, and documentation techniques, involving farmer groups, MSMEs, cooperatives, and the Company's CSR team. MAMI SERA has succeeded in increasing community income by 30%, forming 18 new MSMEs, assisting 27 micro-entrepreneurs, planting 5,200 mangrove seedlings, and building three community waste processing units. The Community Development strategy implemented includes empowerment based on local potential (milkfish and its processed products), innovation in low-cost feed technology and waste processing, strengthening community capacity and skills through integrated training, strengthening economic institutions through the Trengginas Jaya Abadi Cooperative, supporting infrastructure development such as toilets and wastewater treatment plants, increasing market access through modern packaging and digital promotion, and integration with the sustainable development agenda and the Sustainable Development Goals (SDGs). The main obstacles faced are limited land for production facilities and the need to optimize product marketing strategies.